Interactions between the jasmonic and salicylic acid pathway modulate the plant metabolome and affect herbivores of different feeding types. (11th February 2014) - SCHWEIGER, R.; HEISE, A.‐M.; PERSICKE, M.; MÜLLER, C.
Abstract The phytohormones jasmonic acid (JA) and salicylic acid (SA) mediate induced plant defences and the corresponding pathways interact in a complex manner as has been shown on the transcript and proteine level. Downstream, metabolic changes are important for plant–herbivore interactions. This study investigated metabolic changes in leaf tissue and phloem exudates of Plantago lanceolata after single and combined JA and SA applications as well as consequences on chewing‐biting (Heliothis virescens) and piercing‐sucking (Myzus persicae) herbivores. Targeted metabolite profiling and untargeted metabolic fingerprinting uncovered different categories of plant metabolites, which were influenced in a specific manner, indicating points of divergence, convergence, positive crosstalk and pronounced mutual antagonism between the signaling pathways. Phytohormone‐specific decreases of primary metabolite pool sizes in the phloem exudates may indicate shifts in sink–source relations, resource allocation, nutrient uptake or photosynthesis. Survival of both herbivore species was significantly reduced by JA and SA treatments. However, the combined application of JA and SA attenuated the negative effects at least against H. virescens suggesting that mutual antagonism between the JA and SA pathway may be responsible. Pathway interactions provide a great regulatory potential for the plant that allows triggering of appropriate defences when attacked by different antagonist species.